LMS Affects Teaching Effectiveness: Depending on LMS Platforms, Lecturer Qualification, and Lecturer Age - Olii, Djami; Manoppo, Christine; Mamahit, Calvin; Abast, Metri (Jurnal Pendidikan Progresif, 2023)
LMS Affects Teaching Effectiveness: Depending on LMS Platforms, Lecturer Qualification, and Lecturer Age. The ability of lecturers to manage the LMS affects the effectiveness of their teaching. Each LMS platform has differences in the user interface and the available features. Educational qualifications and the age of lecturers affect the mastery of LMS applications. So, the type of LMS platform, educational qualifications, and age of the lecturers affect teaching effectiveness. Objective: This study aims to examine the effects and comparisons between the three groups. Methods: The comparison of the LMS platform group consists of Moodle and Google Classroom; the educational qualification group consists of master's and doctoral degrees; and the age group is ≤ 45 years and > 45 years. Findings: The analysis results with the three-way ANOVA found that the three groups had an interaction effect of 74% on the effectiveness of their teaching. Conclusion: LMS Moodle, doctoral educational qualifications, and younger lecturers (≤45 years) have a higher average of lecturer teaching effectiveness. Keywords: LMS, learning management system, lecturer qualification, lecturer age, teaching effectiveness.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202341